Research progress of drug eluting balloon in arterial circulatory system - Lu, Keji; Ye, Xianglin; Chen, Yaoxuan; Wang, Peng; Gong, Meiting; Xuan, Bing; Tang, Zhaobing; Li, Meiling; Hou, Jun; Peng, Ke; Pei, Haifeng (Frontiers in Cardiovascular Medicine, 2024)
The arterial circulatory system diseases are common in clinical practice, and their treatment options have been of great interest due to their high morbidity and mortality. Drug-eluting balloons, as a new type of endovascular interventional treatment option, can avoid the long-term implantation of metal stents and is a new type of angioplasty without stents, so drug-eluting balloons have better therapeutic effects in some arterial circulatory diseases and have been initially used in clinical practice. In this review, we first describe the development, process, and mechanism of drug-eluting balloons. Then we summarize the current studies on the application of drug-eluting balloons in coronary artery lesions, in-stent restenosis, and peripheral vascular disease. As well as the technical difficulties and complications in the application of drug-eluting balloons and possible management options, in order to provide ideas and help for future in-depth studies and provide new strategies for the treatment of more arterial system diseases.